The Effects of VAK Learning Style and Input Type on Causative Construction Development by Iranian EFL Learners - Motahar Tavakoly; Gholamreza Kiany; Seyyed Mohammad Reza Hashemi (Issues in Language Teaching, 2018)
Long’s Interactional Input Hypothesis and Smith’s Input Enhancement Hypothesis hold both foci on Zellig Harris's (1976) formalist approach. Accordingly, the pivotal role of learner’s attention as one of the subcomponents of focus-on-form approach may have confused instruction types. However, whether such learning theories on drawing learners' attention on target language forms suit all types of learners, has not been adequately investigated. Of interest were to explore the significant effect of the two input types as interactionally modified input (IM) and textual input enhancement (TIE) and the interactional effect of learning styles of either visual, auditory, or kinesthetic (VAK) style on knowledge gain of causative constructions. A hundred and twenty female subjects were selected as a homogenous sample out of the 300-member population based on the TOEFL test. A pretest and two posttests were conducted immediately and about one month after the instructional interventions based on either IM technique or TIE technique. To address research questions, two paired samples t-tests and a two-way ANOVA were conducted. Considering the learner’s VAK learning style, the results revealed TIE and IM techniques positively facilitated the development of knowledge of the target features immediately after the instructional interventions. The results, however, failed to indicate the merging effect of the two input types of the study with the leaner’s VAK learning style and the learner’s gain of target grammar knowledge marginally decreased over time. The findings may contribute to the understanding of the integration of learning styles and input-based instructional programs in foreign language education policy.